Go-kart chassis's design and construction based on theoretical and experimental findings - Ho, Yoong Chow (Universiti Malaysia Sarawak (UNIMAS), 2001)
The best way to evaluate a functioning go-kart would be testing its performance under various conditions and points. Therefore, a new go-kart called MechTech-Initial was presented in this report.